On the technical challenges of cognitive radio in TV white spaces - Lodro, Mir Muhammad (2015)
Cognitive Radio (CR) has been considered as a powerful technique to increase the spectral efficiency by enabling unlicensed users to access unused spectrum opportunistically. Cognitive Radio has two important paradigms to efficiently utilise spectrum which are spectrum sensing and spectrum database. In spectrum sensing unlicensed users sense the spectrum and to detect the availability of under-utilised channels before transmission and access the channels when idle or tolerable interference to primary user (PU) is guaranteed. For the later case i.e. database paradigm of CR unlicensed users can acquire the availability of channels through spectrum database before accessing the channels. In this work, spectrum sensing part of the CR has been focused. In cognitive radio SU should yield maximum throughput and guarantee maximum PU protection. Sensing-throughput tradeoff has been studied for both single cognitive radio and cooperative cognitive radio with different fusion strategies. In cooperative cognitive radio OR and Optimal fusion strategies yielded maxim throughput than the AND strategy. Thereafter, the problem of throughput has been compared for both half-duplex cognitive radio and full-duplex cognitive radio for a given target probability of detection. It was found that there is an optimal sensing time at which a CR yields maximum throughput for a given target probability of detection. Much of the initial discussion is based on half-duplex communication cognitive radio (HDC-CR) using HDC-SS scheme. It is of special interest to derive the PD, PFA mathematical expressions for full-duplex communication cognitive radio (FDC-CR) which uses full-duplex spectrum sensing scheme to do sensing and transmission at the same time. It was found that the FDC-CR yields higher throughput for SU than the HDC-CR since FDC-CR performs sensing and data transmission at the same time therefore it gets increased data transmission time for secondary user.